2015
DOI: 10.1371/journal.pone.0130898
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Intracellular and Extracellular ROS Levels in Atherosclerotic Mouse Aortas Ex Vivo: Effects of Lipid Lowering by Diet or Atorvastatin

Abstract: ObjectiveThe first objective was to investigate if intracellular and extracellular levels of reactive oxygen species (ROS) within the mouse aorta increase before or after diet-induced lesion formation. The second objective was to investigate if intracellular and extracellular ROS correlates to cell composition in atherosclerotic lesions. The third objective was to investigate if intracellular and extracellular ROS levels within established atherosclerotic lesions can be reduced by lipid lowering by diet or ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Such latent propensity of lipid-free apoA-I to form amyloids has important physiologic implications, as all the components and conditions needed for inducing amyloid formation by nonoxidized apoA-I exist within the atherosclerotic lesions: MPO (98), active oxygen species (99), lower pH (100), and a higher than in circulation concentration of lipid-free apoA-I (24). This amyloidogenic activity would remove functional protein and deposit amyloid material within the atherosclerotic plaques, a process whose contribution to atherosclerosis progression is presently unknown but postulated to correlate with the incidence of the disease (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Such latent propensity of lipid-free apoA-I to form amyloids has important physiologic implications, as all the components and conditions needed for inducing amyloid formation by nonoxidized apoA-I exist within the atherosclerotic lesions: MPO (98), active oxygen species (99), lower pH (100), and a higher than in circulation concentration of lipid-free apoA-I (24). This amyloidogenic activity would remove functional protein and deposit amyloid material within the atherosclerotic plaques, a process whose contribution to atherosclerosis progression is presently unknown but postulated to correlate with the incidence of the disease (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Abundant evidences have confirmed that uptake of ox‐LDL by macrophages to form foam cells is another main determinant for the endothelial dysfunction and development of atherosclerosis (Angelovich et al, ; Chistiakov et al, ). These lipid‐laden macrophages have been reported to generate various inflammatory cytokines which exert inflammatory response and aggravate the progression of atherosclerosis (Eaton et al, ; Ekstrand et al, ; Manea et al, ; Signorelli et al, ). Therefore, we also delineated the anti‐inflammatory effects of Ginkgolide B in ox‐LDL activated RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…These macrophages have been shown to produce various inflammatory cytokines such as interleukin (IL)‐1 and IL‐2 which exert inflammatory response and aggravate the progression of atherosclerosis (Eaton, Yang, Giachelli, & Scatena, ; Signorelli, Fiore, & Malaponte, ). Moreover, these inflammatory cytokines could further trigger macrophages to produce excess amount of reactive oxygen species (ROS), which also contribute to the plaque formation during the development of atherosclerosis (Ekstrand et al, ; Manea et al, ). This notion is supported by the fact that nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is an important source of ROS in multiple cell types, and the expression of NADPH oxidases is up‐regulated in the cardiovascular diseases and in atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] During atherosclerosis progression, the excessive ROS level induces oxidative stress and the formation of oxidized low‐density lipoprotein (Ox‐LDL) leading to the proliferation of macrophages and vascular smooth muscle cells (VSMCs) to engulf the continuous generation of Ox‐LDL. In advanced atherosclerotic lesions, intracellular and extracellular ROS levels increased, [ 6 ] thus opening big opportunities to develop intelligent drug delivery systems that are responsive toward a biologically relevant environment of inflamed blood vessels for enhancing drug delivery. [ 7–9 ]…”
Section: Introductionmentioning
confidence: 99%